Functional characterization of novel ABCB6 mutations and their clinical implications in familial pseudohyperkalemia - Immacolata Andolfo; Roberta Russo; Francesco Manna; Gianluca De Rosa; Antonella Gambale; Soha Zouwail; Nicola Detta; Catia Lo Pardo; Seth L. Alper; Carlo Brugnara; Alok K. Sharma; Lucia De Franceschi; et al. (Haematologica, 2016)
Isolated familial pseudohyperkalemia is a dominant red cell trait characterized by cold-induced ‘passive leak’ of red cell potassium ions into plasma. The causative gene of this condition is ABCB6, which encodes an erythrocyte membrane ABC transporter protein bearing the Langereis blood group antigen system. In this study analyzing three new families, we report the first functional characterization of ABCB6 mutants, including the homozygous mutation V454A, heterozygous mutation R276W, and compound heterozygous mutations R276W and R723Q (in trans). All these mutations are annotated in public databases, suggesting that familial pseudohyperkalemia could be common in the general population. Indeed, we identified variant R276W in one of 327 random blood donors (0.3%). Four weeks’ storage of heterozygous R276W blood cells resulted in massive loss of potassium compared to that from healthy control red blood cells. Moreover, measurement of cation flux demonstrated greater loss of potassium or rubidium ions from HEK-293 cells expressing ABCB6 mutants than from cells expressing wild-type ABCB6. The R276W/R723Q mutations elicited greater cellular potassium ion efflux than did the other mutants tested. In conclusion, ABCB6 missense mutations in red blood cells from subjects with familial pseudohyperkalemia show elevated potassium ion efflux. The prevalence of such individuals in the blood donor population is moderate. The fact that storage of blood from these subjects leads to significantly increased levels of potassium in the plasma could have serious clinical implications for neonates and infants receiving large-volume transfusions of whole blood. Genetic tests for familial pseudohyperkalemia could be added to blood donor pre-screening. Further study of ABCB6 function and trafficking could be informative for the study of other pathologies of red blood cell hydration.